Accounting Management Training in an Entrepreneurial Context to Support the Economic System - Solihat, Asri; Hamdani, Nizar Alam; Maulani, Galih Abdul Fatah; Dahlena, Alni (Indonesian Journal of Community Empowerment (IJCE), 2025)
A lack of understanding and skills in proper financial record-keeping makes it difficult for business owners to manage cash flow, determine the cost of goods manufactured, measure business profitability, and access capital from financial institutions. This training method utilizes accounting management training in an entrepreneurial context, which can be delivered through a multifaceted approach, combining formal learning and hands-on practice in the field. This training utilizes a participatory approach, technical guidance, and the use of digital tools. The results of this community service activity identified that a comprehensive and practical accounting management training program is a strategic step to improve the ability of MSMEs to adapt and compete in an increasingly complex market. Accounting management training aims not only to provide technical knowledge but also to strengthen the competitiveness of MSMEs as part of the broader economic system.